Silver particles and preparation method and application thereof
Through the cross-linking reaction of raw materials such as silver salt, reducing agent and organic amine coating agent, silver particles with large specific surface area and regular shape were prepared, which solved the problems of wide distribution of silver powder particle size and low production efficiency in the prior art. Improves conductivity and sintering properties and is suitable for a variety of materials fields.
Patent Information
- Application Number
- CN202411234738.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Among the existing silver powder preparation methods, the silver powder produced by mechanical ball milling method has a wide particle size distribution, irregular shape and many impurities, the evaporative condensation method has low production efficiency, and cannot be produced on a large scale, and it is difficult to prepare silver particles with large specific surface area and regular shape. Influences conductivity and sintering properties.
The raw materials such as silver salt, reducing agent, silver seed, organic amine coating agent and dispersant are used to form a polymer network through the pore structure through cross-linking reaction, which improves the sintering activity and shrinkage rate of silver particles, and prepares a specific surface area. Large, regular-shaped silver particles.
It has achieved high specific surface area and good sintering performance of silver particles, improved conductivity, mechanical strength and photoelectric conversion efficiency, and is suitable for electronics, photovoltaics and pharmaceutical materials, reducing the usage and production cost of silver particles.
Smart Images

Figure CN119259988A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials, and in particular relates to silver particles and a preparation method and application thereof. Background Art
[0002] Conductive paste plays an increasingly important role in the modern electronics and energy industries. For example, in the photovoltaic field, conductive paste is an indispensable material in the production of photovoltaic cells. It is mainly used to prepare the front and back electrodes of the cell to collect and transmit current. With the rapid development of photovoltaic energy, the demand for conductive paste is also growing continuously. Conductive paste is mainly composed of high-purity silver powder, glass system and organic carrier. Silver powder accounts for 70-90% of the cost of photovoltaic silver paste. Therefore, the performance of silver powder affects the conductive paste to a large extent. Among them, the specific surface area of silver powder is an important parameter to measure the coarseness of silver powder particles, which has a significant impact on the performance of silver powder. Increasing the specific surface area of silver powder is conducive to improving conductivity, improving sintering performance, improving activity, and optimizing the printability, adhesion and density of silver powder paste. How to increase the specific surface area of silver powder is one of the current research focuses.
[0003] The preparation methods of silver powder are mainly divided into two categories: physical method and chemical method. The physical method mainly includes: mechanical ball milling method and evaporation condensation method. The disadvantage of silver powder prepared by mechanical ball milling method is that the silver powder particle size distribution is wide, the shape is irregular, and impurities may be introduced; the evaporation condensation method has low production efficiency and cannot be mass-produced. Therefore, it is urgent to find a silver particle with large specific surface area, regular shape, simple preparation process and low cost. Summary of the invention
[0004] In order to overcome at least one of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a silver particle having a large specific surface area, good electrical conductivity and sintering performance.
[0005] A second object of the present invention is to provide a method for preparing the above-mentioned silver particles.
[0006] A third object of the present invention is to provide a silver sintered body.
[0007] A third object of the present invention is to provide an application of the above-mentioned silver particles or silver sintered body.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a silver particle, comprising the following preparation raw materials: a silver salt, a reducing agent, a silver seed, an organic amine coating agent, a dispersant, and a flocculant, wherein the carbon number of the organic amine coating agent is greater than or equal to 6.
[0010] The reaction mechanism of the present invention is mainly to reduce the silver salt to silver atoms by using a reducing agent, and to make the silver atoms adhere to silver seed crystals to grow into silver particles. Among them, an organic amine coating agent is used as one of the raw materials for preparing the silver particles. In combination with other raw materials, it is beneficial to form a polymer network with a through-pore structure through a cross-linking reaction during the preparation of the silver particles. The structure can help the organic raw materials to quickly escape during the sintering of the silver particles without being retained in the silver particles to affect the sintering performance, thereby improving the sintering activity and sintering shrinkage rate of the silver particles.
[0011] Preferably, the carbon number of the organic amine capping agent is 6-30; more preferably, the carbon number of the organic amine capping agent is 7-28; even more preferably, the carbon number of the organic amine capping agent is 8-25.
[0012] Preferably, the organic amine coating agent includes at least one of octylamine, hexadecylamine, octadecylamine, trihexylamine, bis(hydroxyethyl)oleylamine, diallylamine or triisopropanolamine; further preferably, the organic amine coating agent includes at least one of octylamine, bis(hydroxyethyl)oleylamine, diallylamine or triisopropanolamine; even further preferably, the organic amine coating agent includes bis(hydroxyethyl)oleylamine, triisopropanolamine or a combination thereof.
[0013] In some specific embodiments of the present invention, the organic amine capping agent is selected from triisopropanolamine.
[0014] Preferably, the reducing agent comprises at least one of ascorbic acid, citric acid, sodium citrate, potassium citrate or glucose; further preferably, the reducing agent comprises at least one of ascorbic acid, sodium citrate or glucose; further preferably, the reducing agent is selected from ascorbic acid.
[0015] In some specific embodiments of the present invention, the reducing agent is used as a preparation raw material in the form of a solution.
[0016] In some specific embodiments of the present invention, the solvent of the reducing agent solution is water.
[0017] Preferably, the silver salt comprises at least one of silver nitrate, silver fluoride, silver chlorate or silver perchlorate; further preferably, the silver salt comprises at least one of silver nitrate, silver chlorate or silver perchlorate; further preferably, the silver salt is selected from silver nitrate.
[0018] In some specific embodiments of the present invention, the silver salt is prepared in the form of a solution.
[0019] In some specific embodiments of the present invention, the solvent of the silver salt solution is water.
[0020] Preferably, the silver ion concentration of the silver salt solution is 0.01 to 5 mol / L; more preferably, it is 0.03 to 4.5 mol / L; and more preferably, it is 0.08 to 2 mol / L.
[0021] Preferably, the dispersant comprises at least one of polysorbate, polyacrylic acid or styrene maleate; further preferably, the dispersant is selected from polysorbate.
[0022] Preferably, the polysorbate includes at least one of polysorbate 20, polysorbate 40, polysorbate 60 or polysorbate 80; further preferably, the polysorbate is selected from polysorbate 60.
[0023] Preferably, the flocculant includes at least one of lauric acid, sodium laurate, potassium laurate or stearic acid; further preferably, the flocculant includes at least one of lauric acid, sodium laurate or stearic acid; further preferably, the flocculant is selected from sodium laurate.
[0024] Preferably, the average particle size of the silver seed crystals is 100 to 300 nm; more preferably, 150 to 250 nm; and even more preferably, 150 to 200 nm.
[0025] Preferably, the silver content of the silver seed crystal is 1 to 15 wt %; more preferably, it is 3 to 10 wt %; and even more preferably, it is 4 to 8 wt %.
[0026] Preferably, the molar ratio of the reducing agent to the silver ions in the silver salt is (0.1-3):1; more preferably (0.4-2.5):1; and even more preferably (0.5-2):1.
[0027] Preferably, the molar ratio of the organic amine coating agent to the silver ions in the silver salt is (0.005-0.4):1; more preferably (0.01-0.35):1; and even more preferably (0.05-0.3):1.
[0028] Preferably, the mass ratio of the dispersant to the silver ions in the silver salt is (0.005-0.06):1; more preferably (0.008-0.055):1; and even more preferably (0.01-0.05):1.
[0029] Preferably, the mass ratio of the flocculant to the silver ions in the silver salt is (0.0005-0.03):1; more preferably (0.001-0.02):1; and even more preferably (0.001-0.01):1.
[0030] Preferably, the mass ratio of silver in the silver seed crystal to silver ions in the silver salt is (0.001-0.02):1; more preferably (0.003-0.015):1; and even more preferably (0.005-0.01):1.
[0031] Preferably, the average particle size of the silver particles is 1 to 5 μm; more preferably 1.5 to 4 μm; and even more preferably 2 to 3 μm.
[0032] Preferably, the specific surface area of the silver particles is ≥ 0.7 m 2 / g; more preferably 0.7 to 2m 2 / g; more preferably 0.7 to 1m 2 / g.
[0033] Preferably, the tap density of the silver particles is ≥5 g / cm 3 ; More preferably 5 to 10 g / cm 3 .
[0034] Preferably, the interior of the silver particles has a through-hole structure.
[0035] The second aspect of the present invention provides a method for preparing the silver particles described in the first aspect of the present invention, comprising the following steps: mixing the various preparation raw materials and subjecting them to a reduction reaction, and obtaining the silver particles after precipitation.
[0036] Preferably, the mixing method is selected from stirring.
[0037] Preferably, the stirring speed is 120 to 480 r / min; more preferably 150 to 450 r / min; further preferably 180 to 410 r / min.
[0038] Preferably, the drying temperature is 30 to 140°C; more preferably 40 to 120°C; and even more preferably 55 to 95°C.
[0039] Preferably, the drying time is 0.5 to 15 hours; more preferably 1 to 12 hours; and even more preferably 4 to 9 hours.
[0040] Preferably, the preparation method of the silver particles specifically comprises the following steps: firstly mixing silver seeds, a reducing agent and an organic amine coating agent, then adding a silver salt and a dispersant for reduction reaction, and finally adding a flocculant for precipitation to obtain the silver particles.
[0041] In some specific embodiments of the present invention, the following steps are further included after precipitation: solid-liquid separation to obtain a precipitate, and the precipitate is dried to obtain the silver particles.
[0042] The third aspect of the present invention provides a silver sintered body obtained by sintering the silver particles described in the first aspect of the present invention.
[0043] The silver particles of the first aspect of the present invention have good sintering performance, especially good sintering activity and sintering shrinkage. The silver sintered body obtained by sintering the silver particles has good density, high mechanical strength, good chemical reaction activity, conductive efficiency and photoelectric conversion efficiency.
[0044] The fourth aspect of the present invention provides a use of the silver particles described in the first aspect of the present invention, or the silver sintered body described in the third aspect of the present invention in the preparation of electronic materials, photovoltaic cell materials, pharmaceutical materials or catalytic materials.
[0045] In some specific embodiments of the present invention, the electronic material includes at least one of a wire, a circuit board, a capacitor, a resistor or a conductive film.
[0046] In some specific embodiments of the present invention, the photovoltaic cell material includes a photovoltaic electrode.
[0047] In some specific embodiments of the present invention, the medical material comprises at least one of an implant material, a drug delivery material, a scaffold material or a medical adhesive material.
[0048] In some specific embodiments of the present invention, the catalytic material includes a catalyst, a catalyst support or a combination thereof.
[0049] The beneficial effects of the present invention are as follows: the present invention utilizes the combination of an organic amine coating agent and other preparation raw materials to obtain silver particles with regular shape, narrow particle size distribution, good dispersibility, large specific surface area, and good sintering performance, thereby facilitating the improvement of the compactness, mechanical strength, conductivity, and photoelectric performance of the silver sintered body. The silver particles or silver sintered body obtained by the present invention have a wide range of applications in the preparation of electronic materials, photovoltaic cell materials, pharmaceutical materials, or catalytic materials.
[0050] Specifically, compared with the prior art, the present invention has the following advantages:
[0051] 1. The silver particles obtained by the present invention have a large specific surface area and a small particle size, which is conducive to increasing the contact area between the silver particles, thereby improving the conductivity; and the silver particles have a large specific surface area and are more easily combined together during the sintering process, thereby forming a denser sintered body structure, thereby improving the mechanical strength and conductivity of the sintered body.
[0052] 2. Silver particles with high specific surface area have higher activity, which is beneficial to increase the reaction rate in chemical reactions. For example, in the field of photovoltaic cells, silver particles with high specific surface area are beneficial to improve the conductivity of electrodes, thereby improving the photoelectric conversion efficiency.
[0053] 3. When preparing conductive silver paste, silver particles with high specific surface area can improve the printability, adhesion and density of the paste.
[0054] 4. Due to the high activity and conductivity of high specific surface area silver particles, the amount of silver particles used can be reduced, the cost can be reduced, and it is conducive to large-scale industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a SEM image of the silver particles of Example 1.
[0056] Figure 2 This is the SEM image of the silver particles in Example 2.
[0057] Figure 3 This is the SEM image of the silver particles in Example 3.
[0058] Figure 4 This is a SEM image of the silver particles of Example 4.
[0059] Figure 5 This is the SEM image of the silver particles in Example 5.
[0060] Figure 6 This is the SEM image of the silver particles of Comparative Example 1.
[0061] Figure 7 This is the SEM image of the silver particles of Comparative Example 2.
[0062] Figure 8 This is the SEM image of the silver particles in Comparative Example 3.
[0063] Fig. 9 This is the SEM image of the silver particles of Comparative Example 4.
[0064] Fig.10 This is the SEM image of the silver particles in Comparative Example 5. DETAILED DESCRIPTION
[0065] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples and comparative examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.
[0066] Example 1
[0067] A silver particle is prepared by the following steps:
[0068] S1, add 128.6675 mL of deionized water into a 250 mL beaker, add 2.6 g of ascorbic acid (VC) solution thereto, start stirring (speed 350 rpm), then add 27 μL of nano silver seed solution (wherein the silver content is 4.5 wt %, and the average particle size of the silver seed is 175 nm), and then immediately add 0.6056 g of triisopropanolamine solution to obtain S1 mixed solution;
[0069] S2, add 0.069 g of polysorbate 60 solution to the S1 mixed solution, and then immediately add 8 mL of silver nitrate solution and mix and stir to obtain the S2 mixed solution;
[0070] S3. Add 0.0138 g of sodium laurate to the mixed solution in S2, stir for 15 min, and then perform solid-liquid separation, wash, and dry (drying temperature is 55° C., drying time is 4.5 h) to obtain silver particles.
[0071] The preparation process of the above-mentioned solution is as follows:
[0072] Silver nitrate solution: Dissolve 5 g of silver nitrate solid in 18.5 mL of deionized water. Since 128.6675 mL of deionized water was added to the beaker in advance, the silver ion concentration in the prepared silver nitrate solution was 0.2 mol / L. Take 8 mL of silver nitrate solution, so the amount of silver ions added to the reaction system is 1.6×10 -3 mol.
[0073] VC solution: In the VC solution, the mass fraction of VC is 6.5%, and the molar ratio of VC to silver ions in the reaction system is 0.6:1;
[0074] Polysorbate 60 solution: In the polysorbate 60 solution, the mass fraction of polysorbate 60 is 5%, and the mass ratio of the dispersant to the silver ions in the reaction system is 0.02:1;
[0075] Configuration of triisopropanolamine solution: in the triisopropanolamine solution, the mass fraction of triisopropanolamine is 5%, and the molar ratio of triisopropanolamine to silver ions in the reaction system is 0.1:1;
[0076] Preparation of sodium laurate solution: In the sodium laurate solution, the mass fraction of sodium laurate is 2.5%, and the mass ratio of sodium laurate to silver ions in the reaction system is 0.002:1;
[0077] Configuration of the nano-silver seed solution: the silver content of the nano-silver seed solution is 4.5 wt %, and the mass ratio of the silver content of the nano-silver seed solution to the silver ions in the reaction system is 0.007:1.
[0078] Example 2
[0079] A silver particle. Compared with Example 1, the silver ion concentration of the silver nitrate solution in this example is 0.1 mol / L, and other raw materials and preparation methods are the same as those in Example 1.
[0080] Example 3
[0081] A silver particle. Compared with Example 1, in this example, the molar ratio of VC to silver ions in the reaction system is 1.2:1, and other raw materials and preparation methods are the same as those in Example 1.
[0082] Example 4
[0083] A silver particle. Compared with Example 1, in this example, the molar ratio of polysorbate 60 to silver ions in the reaction system is 1.2:1, and other raw materials and preparation methods are the same as those in Example 1.
[0084] Example 5
[0085] A silver particle. Compared with Example 1, in this example, the mass ratio of sodium laurate to silver ions in the reaction system is 0.001:1, and other raw materials and preparation methods are the same as those in Example 1.
[0086] Comparative Example 1
[0087] A silver particle. Compared with Example 1, the triisopropanolamine solution is replaced by an acetic acid solution in this example, and other raw materials and preparation methods are the same as those in Example 1.
[0088] Comparative Example 2
[0089] A silver particle. Compared with Example 1, the triisopropanolamine solution is replaced by pentylamine solution in this example, and other raw materials and preparation methods are the same as those in Example 1.
[0090] Comparative Example 3
[0091] A silver particle. Compared with Example 1, the triisopropanolamine solution is replaced by ethylenediamine solution in this example, and other raw materials and preparation methods are the same as those in Example 1.
[0092] Comparative Example 4
[0093] A silver particle. Compared with Example 1, in this example, the molar ratio of triisopropanolamine to silver ions in the reaction system is 0.5, and other raw materials and preparation methods are the same as those in Example 1.
[0094] Comparative Example 5
[0095] A silver particle, compared with Example 1, the stirring speed in this example is 500 rpm, and other raw materials and preparation method are the same as Example 1.
[0096] Performance Characterization
[0097] The silver particles obtained in Examples 1 to 5 and Comparative Examples 1 to 5 were tested for particle size and specific surface area (the particle size was tested using the instrument Anton Paar PSA, and the test method was the humidity measurement method; the specific surface area was tested using the instrument Anton Paar BET, and the test method was the static volume method), and the morphology was characterized using a scanning electron microscope. The particle size and specific surface area data are shown in Table 1, and the scanning electron microscope image is shown in Figures 1 to 10 As shown, Figure 1 is a SEM image of the silver particles of Example 1, Figure 2 is a SEM image of the silver particles of Example 2, Figure 3 is a SEM image of the silver particles of Example 3, Figure 4 is a SEM image of the silver particles of Example 4, Figure 5 is a SEM image of the silver particles of Example 5, Figure 6 is the SEM image of the silver particles of Comparative Example 1, Figure 7 is the SEM image of the silver particles of Comparative Example 2, Figure 8 is the SEM image of the silver particles of Comparative Example 3, Fig. 9 is the SEM image of the silver particles of Comparative Example 4, Fig.10 This is the SEM image of the silver particles in Comparative Example 5.
[0098] Table 1 Particle size and specific surface area data of silver particles in Examples 1 to 5 and Comparative Examples 1 to 5
[0099]
[0100] From Table 1 and Figures 1 to 10 It can be seen that compared with Comparative Examples 1 to 5, the silver particles of Examples 1 to 5 have regular shapes, good dispersibility, and larger specific surface areas. Figure 6 It can be seen that in Comparative Example 1, the acid coating agent such as acetic acid is used, and the silver particles obtained cannot form a through-hole structure, resulting in a small specific surface area. Figures 7-8 It can be seen that in Comparative Examples 2 and 3, organic amines with short carbon chain lengths are used as coating agents, and it is also difficult to form a through-hole structure, and their specific surface areas are small. Figures 9-10 It can be seen that the use of specific dosage ratios and preparation conditions is conducive to obtaining silver particles with a larger specific surface area.
[0101] Furthermore, the silver particles of Examples 1 to 5 have good sintering activity and sintering shrinkage.
[0102] The silver particles of Examples 1 to 5 are sintered to obtain a silver sintered body having good compactness, mechanical strength, electrical conductivity and photoelectric properties.
[0103] The obtained silver particles or silver sintered bodies are used as electronic materials such as wires, circuit boards, capacitors, resistors or conductive films, or photovoltaic cell materials such as photovoltaic electrodes, or medical materials such as implant materials, drug delivery materials, stent materials or medical adhesive materials, or catalytic materials such as catalysts and catalyst carriers, all of which have good application performance. For example, in the field of photovoltaic cells, silver particles with high specific surface area are conducive to improving the conductivity of electrodes, thereby improving the photoelectric conversion efficiency. In addition, when preparing conductive silver paste, silver particles with high specific surface area can improve the printability, adhesion and compactness of the paste.
[0104] The silver particles obtained in the embodiment of the present invention have a large specific surface area and a small particle size, which is conducive to increasing the contact area between the silver particles, thereby improving the conductivity; and the silver particles have a large specific surface area and are easier to combine together during the sintering process, thereby forming a denser sintered body structure, thereby improving the mechanical strength and conductivity of the sintered body. In addition, the silver particles with a high specific surface area obtained in the embodiment of the present invention have a higher activity, which is conducive to improving its reaction rate in chemical reactions. Due to the high activity and conductivity of the high specific surface area silver particles, the amount of silver particles used can be reduced, the cost can be reduced, and it is conducive to large-scale industrial applications.
[0105] In summary, the present invention utilizes the combination of an organic amine coating agent and other preparation raw materials to obtain silver particles with regular shape, narrow particle size distribution, good dispersibility, large specific surface area, and good sintering performance, which is beneficial to improving the density, mechanical strength, conductivity and photoelectric properties of the silver sintered body. The silver particles or silver sintered body obtained by the present invention have wide applications in the preparation of electronic materials, photovoltaic cell materials, pharmaceutical materials or catalytic materials.
Claims
1. A silver particle, characterized in that: The preparation method comprises the following raw materials: silver salt, reducing agent, silver seed, organic amine coating agent, dispersant and flocculant, wherein the carbon number of the organic amine coating agent is greater than or equal to 6.
2. The silver particles according to claim 1, characterized in that The organic amine coating agent includes at least one of octylamine, hexadecylamine, octadecylamine, trihexylamine, bis(hydroxyethyl)oleylamine, diallylamine or triisopropanolamine.
3. The silver particles according to claim 1, characterized in that The reducing agent includes at least one of ascorbic acid, citric acid, sodium citrate, potassium citrate or glucose; and / or, the silver salt comprises at least one of silver nitrate, silver fluoride, silver chlorate or silver perchlorate; and / or, the dispersant comprises at least one of polysorbate, polyacrylic acid or styrene maleate; And / or, the flocculant includes at least one of lauric acid, sodium laurate, potassium laurate or stearic acid.
4. The silver particles according to claim 1, characterized in that The average particle size of the silver seed is 100 to 300 nm; And / or, the silver content of the silver seed crystal is 1 to 15 wt %.
5. The silver particles according to claim 1, characterized in that The molar ratio of the reducing agent to the silver ions in the silver salt is (0.1-3):1; And / or, the molar ratio of the organic amine coating agent to the silver ions in the silver salt is (0.005-0.4):1; And / or, the mass ratio of the dispersant to the silver ions in the silver salt is (0.005-0.06):1; And / or, the mass ratio of the flocculant to the silver ions in the silver salt is (0.0005-0.03):1; And / or, the mass ratio of silver in the silver seed crystal to silver ions in the silver salt is (0.001-0.02):
1.
6. The silver particles according to claim 1, characterized in that The average particle size of the silver particles is 1 to 5 μm; And / or, the specific surface area of the silver particles is ≥ 0.7 m 2 / g; And / or, the interior of the silver particles has a through-hole structure.
7. A method for preparing silver particles according to any one of claims 1 to 6, characterized in that: The following steps are involved: The various raw materials are mixed and subjected to reduction reaction, and the silver particles are obtained after precipitation.
8. The preparation method according to claim 7, characterized in that: The mixing method is selected from stirring; the stirring speed is 120 to 480 r / min; And / or, the drying temperature is 30 to 140°C; And / or, the drying time is 0.5 to 15 hours.
9. A silver particle sintered body, characterized in that: The invention is obtained by sintering the silver particles according to any one of claims 1 to 6.
10. Use of the silver particles according to any one of claims 1 to 6, or the silver particle sintered body according to claim 9, in the preparation of electronic materials, photovoltaic cells, pharmaceutical materials or catalytic materials.
Citation Information
Patent Citations
Silver particles and preparation method and application thereof
CN116571734A
Flaky and spherical mixed silver powder and preparation method and application thereof
CN117324632A
Silver particles with rough surfaces and preparation method and application thereof
CN118492363A
Silver powder production method
JP2015110826A
Synthesis and optical manipulation method for multi-branched tree-shaped composite nanostructure of plasmonic waveguide
WO2019148707A1